The policy of the United States of America towards NATO 1990-2000 (Journal of Imam Al-Kadhim College, 2023)
Abstract :With the end of the Cold War, serious questions emerged about the importance and feasibility of NATO's existence, particularly after the demise of the threat to the Soviet Union, but the United States worked hard to maintain, maintain, sustain and sustain this alliance because it saw its loss as abandoning its most effective and influential means of European thinking, as well as working together with non-member states, but had the ambition to work at the global level, so the Alliance continued to adapt Its structure and improved capabilities to keep pace with the post-Cold War world, so nato's loss to the United States could be one of the most important justifications for its leadership of Western countries and thus the reversal of this leadership and control over the rest of the world, as well as the U.S. fear that the loss of this alliance could create competition between it and European countries that could lead in the future to conflict among them.So the United States did not separate the European and American security, and made it in one crucible, because it realized that it is impossible to eliminate all international forces, but it is possible to contain these forces through relative participation, which makes them revolve around astronomy and American influence, and the best way to contain the growing power of Europe is NATO, which has made strategic decisions whether the security or political of Europe linked in one way or another to NATO, most of whose decisions are U.S. to ensure clear U.S. influence in these resolutions, thereby limiting European aspirations for common security and foreign political independence.So this research begins to answer the question: How did the United States (NATO) serve its strategic objectives and interests after the danger for which it was created disappeared? It has renewed confidence in the alliance to continue as the main expression of American interests on the European continent, and the main point linking the two sides of the Atlantic, so it has worked to employ the alliance militarily — security, politically, economically, ideologically and technologically to serve its strategic objectives and interests, and to contain competing and potential forces.To answer the above, the overall structure of the research was three investigations. The first is to address the post-Cold War policy of the United States of America towards NATO. The second topic included the policy of the United States of America, NATO and the post-Cold War challenges, while the third was the development of nato's structure by the United States and the search for enemies.
Keywords: the United States of America, NATO, Cold war era